2013
DOI: 10.3171/2013.1.spine12305
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional angioarchitecture of spinal dural arteriovenous fistulas, with special reference to the intradural retrograde venous drainage system

Abstract: Object There have been significant advances in understanding the angioarchitecture of spinal dural arteriovenous fistulas (AVFs). However, the major intradural retrograde venous drainage system has not been investigated in detail, including the most proximal sites of intradural radiculomedullary veins as they connect to the dura mater, which are the final targets of interruption in both microsurgical and endovascular treatments. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…For example, the angioarchitecture of dural AVFs in the thoracic region differs from that in conus/lumbar lesions. 25) The proposed classification system does not include anatomical differences at each spinal level. Furthermore, there may be another type of spinal AV shunt that does not fit any type of this classification.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the angioarchitecture of dural AVFs in the thoracic region differs from that in conus/lumbar lesions. 25) The proposed classification system does not include anatomical differences at each spinal level. Furthermore, there may be another type of spinal AV shunt that does not fit any type of this classification.…”
Section: Discussionmentioning
confidence: 99%
“… 20 The vertebral venous plexus has been classically divided into an internal (intradural) vertebral plexus (which possesses an anterior and a posterior component) and an external (or epidural) vertebral plexus. Recently, it has been demonstrated that the epidural vertebral plexus is closely connected to the intracranial venous sinuses in what could be described as the cerebrospinal venous system, 21 or the so-called extradural neural axis compartment. 22…”
Section: Discussionmentioning
confidence: 99%
“…Hiu et al [11] used 3DRA to obtain reliable visualization of fistulous points in patients with SDAVF and reported that detailed information including small vessels and osseous structures could be delineated. Takai et al [12] investigated the relationship between the major intradural retrograde venous drainage system and intradural neural structures by using operative video recordings and 3DRA images, and found spinal dural AVFs are not always dorsal types. Suh et al [13] also demonstrated 3DRA for evaluating angioarchitecture in patients with SDAVF.…”
Section: Discussionmentioning
confidence: 99%